Detrital-zircon geochronology and provenance of the Ocloyic synorogenic clastic wedge, and Ordovician accretion of the Argentine Precordillera terrane - Thomas, William A. (2015)
The Precordillera terrane in northwestern Argentina is interpreted to be anexotic (Laurentian) continental fragment that was accreted to western Gondwanaduring the Ordovician. One prominent manifestation of the subductionand collision process is a Middle?Upper Ordovician clastic wedge, which overliesa passive-margin carbonate-platform succession in the Precordillera. U/Pbages of detrital zircons from sandstones within the clastic wedge, as well as zirconsfrom clasts within conglomerates, provide documentation for the compositionof the sediment provenance. The ages of detrital zircons are consistentvertically through the succession, as well as laterally along and across strike ofthe Precordillera, indicating a single, persistent sediment source throughoutdeposition of the clastic wedge. The dominant mode (~1350?1000 Ma) of thedetrital-zircon ages corresponds to the ages of basement rocks in the WesternSierras Pampeanas along the eastern side of the Precordillera. A secondarymode (1500?1350 Ma) corresponds in age to the Granite-Rhyolite province ofLaurentia, an age range which is not known in ages of basement rocks of theWestern Sierras Pampeanas; however, detritus from Granite-Rhyolite-age rocksin the basement of the Precordillera was available through recycling of synriftand passive-margin cover strata. Igneous clasts in the conglomerates haveages (647?614 Ma) that correspond to the ages of minor synrift igneous rocks inthe nearby basement massifs; the same ages are represented in a minor mode(~750?570 Ma) of detrital-zircon ages. A quartzite clast in a conglomerate, aswell as parts of the population of detrital zircons, indicates the importanceof a source in the metasedimentary cover of the leading edge of the Precordillera.The Famatina continental-margin magmatic arc reflects pre-collisionsubduction of Precordillera lithosphere beneath the western Gondwana margin;however, no detrital zircons have ages that correspond to Famatina arcmagmatism, indicating that sedimentary detritus from the arc may have beentrapped in a forearc basin and did not reach the foreland. The indicators ofsedimentary provenance for the foreland deposits are consistent with subductionof the Precordillera beneath western Gondwana, imbrication of basementrocks from either the Precordillera or Gondwana into an accretionary complex,and recycling of deformed Precordillera cover rocks.